2017
DOI: 10.1007/s12013-017-0821-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Phytochemicals Targeting c-Met Kinase Domain using Consensus Docking and Molecular Dynamics Simulation Studies

Abstract: c-Met receptor tyrosine kinase is a proto-oncogene whose aberrant activation is attributed to a lower rate of survival in most cancers. Natural product-derived inhibitors known as "fourth generation inhibitors" constitute more than 60% of anticancer drugs. Furthermore, consensus docking approach has recently been introduced to augment docking accuracy and reduce false positives during a virtual screening. In order to obtain novel small-molecule Met inhibitors, consensus docking approach was performed using Aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Molecular docking, molecular dynamics, and virtual screening approaches can now be efficiently used for the design of new inhibitors of the MET kinase domain [27,56,[76][77][78][79][80]. From all these approaches, new potent compounds were obtained and more highlights revealed about MET kinase domain conformational behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular docking, molecular dynamics, and virtual screening approaches can now be efficiently used for the design of new inhibitors of the MET kinase domain [27,56,[76][77][78][79][80]. From all these approaches, new potent compounds were obtained and more highlights revealed about MET kinase domain conformational behavior.…”
Section: Discussionmentioning
confidence: 99%
“…We reasoned that it should be taken into account for designing drugs with improved efficiency and selectivity profiles [25,26]. To be efficient, the molecular docking engines embedded within the virtual screening approaches must be adapted to handle such flexibility [27,28]. In the present work, we used the ensemble-docking strategy-previously recognized for its efficiency in drug design [29]-and show the benefit of an investigation using a large ensemble-docking on MET.…”
Section: Introductionmentioning
confidence: 98%
“…In recent years, an increasing number of studies have demonstrated that several inhibitors can specifically target HGF/c-Met in various types of cancer (38,39). Several c-Met inhibitors are currently under clinical studies (40,41). In addition, HGF analogues, anti-HGF humanized antibodies and c-Met induced receptor antibodies directed against the c-Met extracellular domain are being used to prevent HGF-specific binding and activation of c-Met (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…Other reported strategies for achieving scoring function consensus are sequential docking [117,118], linear regression [119], rank-by-rank, rank-by-number, rank-by-vote [86,107,120] and standard deviation consensus [121]. Combinations of consensus docking strategies and ligand-based approaches have also been suggested [122,123].…”
Section: Consensus Methodsmentioning
confidence: 99%